cultural differences in coordination decisions within interdependent security context - ju, linlin (2009)
Abstract The purpose of this study is to investigate cultural differences in coordination decisions in a coordination game with considering IDS context. IDS context is introduced into a coordination game since it recently draws more and more people’s attention. The concepts of individualism/collectivism as the key aspects of culture variability are introduced into the cultural differences study. It is assumed that Chinese people are more collectivistic and more likely to coordinate each other’s expectation to achieve the payoff dominance equilibrium which brings both of them the best payoff, while European people are more individualistic and are less likely to coordinate at a superior payoff strategy resulting in coordination failure. The research applied self-report survey for data collection. A sample which contains sixty Chinese university students and sixty European university students was controlled. The results indicate that different cultures regarding individualism/collectivism influence people’s coordination decisions when faced coordination problems arising in an IDS context.